Benefits of blood flow restriction trainings for alpine skiing sport - Zinoviev, N. A.; Gromov, M. M.; Bobrov, I. V. (Theory and Practice of Physical Culture, 2019)
Modern Alpine skiing sport reports the highest injury statistics due to the athletes being exposed to the high-intensity shocks and vibrations of negative impact on the body on the whole and the knee joints and spine in particular. That is why the sport community gives a special priority to new training systems to scale down the health risks. The study was designed to test benefits of the traditional strength training versus the blood flow restriction training models in the Alpine skiing sport. Sampled for the model testing experiment were the members of the Saint Petersburg Alpine skiing team (n=16) who had their physical fitness tested prior to and after the experiment by the following tests: squats with maximal weight with knee angle under 90 degrees; and the 90-second stand (51cm high) jumps (count), with alternating jump sides.